There Are Critical Reasons for Not Further Delaying the Implementation of the New ICD-10 Coding System. - Averill, Richard; Bowman, Sue (Journal of AHIMA, 2012)
On April 17, 2012, the Department of Health and Human Services (HHS) published a rule proposing postponement of the implementation date for the International Classification of Diseases, 10th Edition diagnosis codes (ICD-10-CM) and procedure codes (ICD-10-PCS) by one year to October 1, 2014. An article in Health Affairs titled "There Are Important Reasons For Delaying the Implementation Of The New ICD-10 Coding System" asserts that the ICD-10-CM conversion will be "expensive, arduous, disruptive, and of limited direct clinical benefit." Contrary to the conclusions in this article, implementation of the ICD-10-CM and ICD-10-PCS code sets will provide major advantages over the existing ICD-9-CM code set. Implementation is long overdue and will provide significant cost benefits. Any further implementation delay will increase the cost of the transition as well as perpetuate the costs and negative consequences associated with continued reliance on imprecise diagnosis and procedure information.